Experimental investigation into the physico-chemical properties changes of palm biodiesel under common rail diesel engine operation for the elucidation of metal corrosion and elastomer degradation in fuel delivery system - Chandran, Davannendran (2017)
Compatibility of fuel delivery materials (FDM) with biodiesel fuel in the fuel delivery system (FDS) under real-life common rail diesel engine (CRDE) operation poses a challenge to researchers and engine manufacturers alike. Although standard methods such as ASTM G31 and ASTM D471 for metals and elastomers, respectively, are deemed suitable for evaluating the effects of water content, total acid number (TAN) and oxidation products in biodiesel on FDM degradation, they do not resemble the actual engine operation conditions such as varying fuel pressure/temperature as well as the presence of a wide range of materials in the FDS of a diesel engine. Hence, the current allowable maximum 20 vol% of biodiesel with 80 vol% of diesel (B20) for use in diesel engines to date is debatable. Additionally, biodiesel utilization beyond B20 is essential to combat declining air quality and to reduce the dependence on fuel imports. This thesis aims to elucidate the actual compatibility present between FDM and biodiesel in the FDS under real-life CRDE operation. This was achieved through multi-faceted experimentations which commenced with analyses on the deteriorated palm biodiesel samples collected during and after CRDE operation. Next, the fuel properties which should be emphasized based on the deteriorated fuel were determined. This was then followed by ascertaining the effects of the emphasized fuel properties towards FDM degradation. Ultimately, the actual compatibility of FDM with biodiesel under engine operation through modified immersion investigations was determined. FDM degradation acceleration factors such as oxidized biodiesel, TAN and water content were eliminated since these factors were not affected based on the analysed fuel samples collected after engine operation. No oxidation products such as aldehydes, ketones and carboxylic acids were detected while the TAN and water content were within 0.446% and 0.625% of their initial values, respectively. Instead, the biodiesel’s dissolved oxygen (DO) concentration and conductivity value were not only found to have changed during and after engine operation by -93% and 293%, respectively, but were also found to have influenced biodiesel deterioration under engine operation. These two properties were subsequently discovered to have adversely affected FDM degradation independently. The copper corrosion rate and nitrile rubber (NBR) volume change increased by 9% and 13%, respectively, due to 22% increase in the conductivity value. In contrast, the copper corrosion rate and NBR volume swelling reduced by 91% and 27%, respectively, due to 96% reduction in the DO concentration. Ultimately, copper corrosion and NBR degradation were determined to be lowered by up to 92% and 73%, respectively, under modified immersion as compared to typical immersion condition. These outcomes distinctly show that acceptable to good compatibility is present between FDM and biodiesel under CRDE operation. The good compatibility is strongly supported since only a maximum lifespan reduction of 1.5 years is predicted for metal exposed to biodiesel as compared to diesel for a typical component lifespan of 15 years. For the elastomers, acceptable compatibility is found present between elastomer and biodiesel based on the determined 11% volume change which conforms to the tolerance level of elastomer degradation as stated by the elastomer manufacturers. These are especially true for the evaluated metals and elastomers investigated under the modified laboratory immersion which replicates similar conditions to a real-life CRDE. Overall, this work has contributed to the advancement of knowledge and application of biodiesel use in diesel engines.